Optical fiber based light scattering detection in microfluidic droplets - Wohlfeil, Shulin; Hengoju, Sundar; Munser, Anne-Sophie; Tovar, Miguel; Shvydkiv, Oksana; Roth, Martin; Schroeder, Sven; Beckert, Erik; Eberhardt, Ramona; Tuennerman, Andreas (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2019)
Droplet based microfluidic technology is a miniaturized platform for microbial analysis on picoliter scale. With its costefficiency, high-throughput and feasibility of complex handling protocols, droplet microfluidics is a favorable platform for applications such as microorganism screening or synthetic biology. Scattered-light-based microbial detection, in comparison to the widely used fluorescent-label-based approach, provides a contact-free and label-free, yet sensitive measuring solution. The angular dependency of scattered light delivers an elaborate information about the morphology and the physical properties, e.g. size and refractive index, of microbial samples. Due to the complexity and ambiguity of the droplet contents, an angle resolved scattered light detection system could provide powerful method for a label-free identification and quantification of the microbes in droplets. In this paper, a novel approach of light scattering measurement in Polydimethylsiloxane (PDMS) microfluidic chips is presented, engaging optical fibers for a light-scattering-based on-chip microbial detection. Optical fibers, with their fast readout and compact size, are very suitable for easier system integration towards flexible and versatile lab-on-a-chip applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Droplet microfluidics; Light scattering; Optical fiber